Screening for psychiatric morbidity in an accident and emergency department. - Bell, G (1990)
One hundred and twenty A&E Department daytime attenders were screened for psychiatric disorder in a two stage procedure. Thirty-three patients were identified as General Health Questionnaire (GHQ) 'cases' of whom 28 agreed to a psychiatric interview using the Clinical Interview Schedule. Twenty-eight GHQ 'non-cases' were also interviewed. A psychiatric diagnosis was made in 24 patients, 21 of whom were GHQ cases. Patients were more likely to suffer from psychiatric morbidity if the presenting complaint was other than minor trauma. There were trends for psychiatric morbidity to be associated with not being married and living in Bloomsbury Health District (No Fixed Abode or resident) or Northeast London. Sixty-nine percent of cases had a positive past psychiatric history. Ten of 12 cases (83%) requiring primary care intervention were not registered with a GP. It is suggested that appropriate intervention would be for A&E Departments to routinely facilitate such registration. In addition, resources need to be released to make 9am to 5pm walk-in psychiatric services commonplace.